Immune reconstitution and clinical recovery following anti-CD28 antibody (TGN1412)-induced cytokine storm - Panoskaltsis, Nicki; McCarthy, Neil E.; Stagg, Andrew J.; Mummery, Catherine J.; Husni, Mariwan; Arebi, Naila; Greenstein, David; Price, Claire L.; Al-Hassi, Hafid O.; Koutinas, Michalis; Mantalaris, Athanasios A.; Knight, Stella C. (My University, 2021)
Cytokine storm can result from cancer immunotherapy or certain infections, including COVID-19. Though short-term immune-related adverse events are routinely described, longer-term immune consequences and sequential immune monitoring are not as well defined. In 2006, six healthy volunteers received TGN1412, a CD28 superagonist antibody, in a first-in-man clinical trial and suffered from cytokine storm. After the initial cytokine release, antibody effect-specific immune monitoring started on Day + 10 and consisted mainly of evaluation of dendritic cell and T-cell subsets and 15 serum cytokines at 21 time-points over 2 years. All patients developed problems with concentration and memory; three patients were diagnosed with mild-to-moderate depression. Mild neutropenia and autoantibody production was observed intermittently. One patient suffered from peripheral dry gangrene, required amputations, and had persistent Raynaud's phenomenon. Gastrointestinal irritability was noted in three patients and coincided with elevated gamma delta T-cells. One had pruritus associated with elevated IgE levels, also found in three other asymptomatic patients. Dendritic cells, initially undetectable, rose to normal within a month. Naive CD8(+)T-cells were maintained at high levels, whereas naive CD4(+)and memory CD4(+)and CD8(+)T-cells started high but declined over 2 years. T-regulatory cells cycled circannually and were normal in number. Cytokine dysregulation was especially noted in one patient with systemic symptoms. Over a 2-year follow-up, cognitive deficits were observed in all patients following TGN1412 infusion. Some also had signs or symptoms of psychological, mucosal or immune dysregulation. These observations may discern immunopathology, treatment targets, and long-term monitoring strategies for other patients undergoing immunotherapy or with cytokine storm.
Keywords: Cytokine storm; Cytokine release syndrome; TGN1412; Immunotherapy; Immune monitoring; Immune-related adverse events (irAEs)